Identification of an "in vivo" control point in the synthesis of starch in starchy-corn - Flores, Feliciano E.V.; Davies, Michael Desmond (Pesquisa Agropecuaria Brasileira, 2014)
The effect of 3-phosphoglycerate and inorganic pyrophosphate, known activator and inhibitor from in vitro studies of the enzyme ADPG-pyrophosphorylase, was determined in vivo using starchy-corn. The results suggest that above metabolites do modify the activity of the ADPG-pyrophosphorylase, and indicate that conclusions based on in vitro studies do operate in vivo, providing further evidence that this enzymatic step is an important control point in starch biosynthesis.